Introduction. Sex work in the UK - Mavis Maclean (Oñati Socio-Legal Series)
This introduction to the collection of papers on SexWork in the 21st century takes the UK as an example to demonstrate the kinds of data which can be found from which to develop informed argument about the current state of legal regulation and the need for change.